Leptospiral Immunoglobulin-Like Domain Proteins: Roles in Virulence and Immunity - Haake, David A.; Matsunaga, James (Frontiers in Immunology, 2021)
The virulence mechanisms required for infection and evasion of immunity by pathogenic Leptospira species remain poorly understood. The past decade has witnessed the discovery of a number of L. interrogans surface proteins, which lie at the interface between the pathogen and host. Among these proteins, the functional properties of the Lig (leptospiral immunoglobulin-like domain) proteins have been examined most thoroughly. LigA, LigB and LigC contain a series of, 13, 12, and 12 closely-related domains, respectively, each containing a bacterial immunoglobulin (Big) -like fold. The multidomain region forms a mostly elongated structure that exposes a large surface area. Leptospires wield the Lig proteins to promote interactions with a range of specific host proteins, including those that aid evasion of innate immune mechanisms. These diverse binding events mediate adhesion of L. interrogans to the extracellular matrix, inhibit hemostasis, and inactivate key complement proteins. These interactions may help L. interrogans overcome the physical, hematological, and immunological barriers that would otherwise prevent the spirochete from establishing a systemic infection. Despite significant differences in the affinities of the LigA and LigB proteins for host targets, their functions overlap during lethal infection of hamsters; virulence is lost only when both ligA and ligB transcription is knocked down simultaneously. This review serves to summarize current knowledge of Lig protein roles in virulence and immunity and to identify directions needed to better understand the precise roles of the Lig proteins during infection.